2022
DOI: 10.3390/ma15217811
|View full text |Cite
|
Sign up to set email alerts
|

Improved Osseointegration of Selective Laser Melting Titanium Implants with Unique Dual Micro/Nano-Scale Surface Topography

Abstract: Selective laser melting manufacture of patient specific Ti implants is serving as a promising approach for bone tissue engineering. The success of implantation is governed by effective osseointegration, which depends on the surface properties of implants. To improve the bioactivity and osteogenesis, the universal surface treatment for SLM-Ti implants is to remove the primitive roughness and then reengineer new roughness by various methods. In this study, the micro-sized partially melted Ti particles on the SLM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The microtopography affects the early cell adhesion and proliferation, while the nanotopography regulates protein conformation and further modulates osteoblast differentiation. [ 169 ] For the surface modification of SLM porous Ti and its alloys, microtopography is commonly prepared by acid treatment, while nanotopography can be prepared by alkali treatment, sol–gel, CVD, ALD, anodization, and MAO. Furthermore, different methods can be used in combination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The microtopography affects the early cell adhesion and proliferation, while the nanotopography regulates protein conformation and further modulates osteoblast differentiation. [ 169 ] For the surface modification of SLM porous Ti and its alloys, microtopography is commonly prepared by acid treatment, while nanotopography can be prepared by alkali treatment, sol–gel, CVD, ALD, anodization, and MAO. Furthermore, different methods can be used in combination.…”
Section: Discussionmentioning
confidence: 99%
“…[ 163–165 ] Sol–gel is a common surface modification method applied to coat biomaterials on the surface of bone implants, such as TiO 2 , [ 166 ] ZnO, [ 167 ] MgO, [ 168 ] etc. Sun et al [ 169 ] deposited mesoporous bioactive glass (MBG) nanospheres on SLM Ti implant using sol–gel method. The results showed that bioactive ions (Ca, Si) can be continuously and stably released from the MBG nanospheres into SBF.…”
Section: Chemical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appended ZnO was also achieving an excellent antibacterial function (Figure 2b). In one study, Sun et al [29] used selective laser melting technology to prepare the implant which with unique dual micro-and nano-topography. The combinatorial design of micro-Ti particles and mesoporous bioactive glasses (MBG) nano-spheres has the effect of promoting cell adhesion and osteogenic differentiation.…”
Section: The Change Of Topography On the Micronano Scale Affects Oste...mentioning
confidence: 99%
“…Topography Hierarchical micro/nano surface topography Improvement of bioactivity and osteogenic properties [25,27,156] Multi-scale composite structures coated with ZnO were prepared on Ti6Al4V implants Enhanced MC3T3-E1 osteogenesis and bacterial activities [28,31] A hierarchically micro/nano-topographic PEEK with specific functional groups (amino and COOH/COOR) Enhanced osteogenesis and bacterial activities [30] Hydrophilicity Bilayer scaffold of PLGA-g-PCL with low and high content of polyethylene glycol (PEG)…”
Section: Physicochemical Propertiesmentioning
confidence: 99%